GASTRIC MUCOSAL MICROCIRCULATION IN PATIENTS WITH DUODENAL PEPTIC ULCER AGAINST THE BACKGROUND OF ERADICATION THERAPY - Akermi, J.; Andreeva, Y. A. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2015)
The article presents the results of investigation of gastric mucosal microcirculation with the help of laser-Doppler flowmetry in acute phase of duodenal ulcer during 7 and 14-day eradication therapy. The study enabled to obtain some data on effectiveness of the two therapeutic eradication regimens as well as their im-pact on gastric mucosal microcirculation in the process of ulcer defects healing.